Competence and Knowledge Sharing in Police Performance: Workload as a Moderating Variable - P. Putra, Breacman; Kusumastuti, Retno (Jurnal Ilmiah Administrasi Publik, 2023)
The development of information technology has an impact on society but also has an impact on the emergence of cybercrime. To effectively handle cybercrime cases, police must develop the necessary resources and competencies. This development will have a positive impact on police performance. This study aims to analyze the effect of competence and knowledge sharing on police performance and the role of workload in moderating the effect of competence and knowledge sharing on police performance. This study distributed 127 questionnaires to investigators of the cyber sub-directorate at Polda Metro Jaya. The analysis in this study used a structural equation model (SEM). The results of this study indicate that competence and knowledge sharing have a positive and significant effect on police performance, and this study also shows that workload has a negative and insignificant effect in moderating the impact of competence and knowledge sharing on police performance.